Earnings Quality and Corporate Governance in Jordan: An Exploration in a Developing Market Context - Freihat F.A.Y.; Kadir M.R.A.; Kamarudin K.A.; Sapingi R. (World Scientific and Engineering Academy and Society, 2025)
The primary purpose of this research is to examine the impact of corporate governance mechanisms, namely, the board of directors' characteristics (expertise, independence, and directors? remunerations) and AC characteristics (AC Independence, AC Expertise, and AC Activity) on earnings quality in the Jordanian context. Using the Eviews software to analyze panel data of 94 non-financial listed companies from 2015 to 2021, the results revealed that board expertise, board independence, AC Activity, and AC Expertise have significantly negative effects on EM, which reflects that these mechanisms have a significant and positive influence on earnings quality in Jordanian non-financial companies. This supports the predictions of agency theory, which predicts that active audit committees, expert members on the audit committees, and the experience and independence of the board members expect to enhance the quality of earnings. Conversely, the findings show that AC Independence and directors? remuneration have an insignificant effect on EM. The results reveal the critical role of board members and audit committees in enhancing the earnings quality of Jordanian companies. This study suggests that Jordanian policymakers need additional support and enhancement regarding CG mechanisms, particularly in Jordan?s transitioning economy, to attract additional investors. ? 2024, World Scientific and Engineering Academy and Society. All rights reserved.